Managing the Digital Image Restoration Amidts the Faith-Based Crisis : Semiotics and Ethical Decision Making Analysis - Kholifatul Fauziah; Zainal Arifin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Faith-based crises pose significant challenges to global franchise brands, requiring strategic communication approaches to mitigate reputational risks. This study examines McDonald's Indonesia's crisis response amidst the boycott movement triggered by its alleged affiliation with McDonald's Israel during the escalation of the Palestinian-Israeli conflict. Utilizing Roland Barthes' semiotic analysis and Parsons' Ethical Decision-Making (EDM) framework, this research analyzes the representation of messages and ethical considerations in McDonald's Indonesia's official press release on Instagram. Findings reveal that the company employs a neutrality and non-partisanship strategy, emphasizing its independent ownership structure, local employment contributions, and national identity to distance itself from the global franchise network. While this approach aligns with the EDM principles of veracity, non-malfeasance, and beneficence, gaps in transparency and fairness remain potential challenges in public perception. The study contributes to the theoretical understanding of digital image restoration in faith-based crises and offers practical insights for corporate crisis management in profit-oriented organizations. Future research should explore audience reception and public sentiment to provide a more comprehensive assessment of crisis communication effectiveness.